2010
DOI: 10.1016/j.ejor.2009.01.023
|View full text |Cite
|
Sign up to set email alerts
|

A problem-structuring model for analyzing transportation–environment relationships

Abstract: This study proposes a decision support system module for analyzing impacts of transportation policies on environment. The main issues of the contemporary transport models include the specification of the nature. For a sustainable transportation system, the extent of the relationships between transport and the environment has to be considered. For this purpose a two-stage problem structuring model is developed. Initially, experts' opinions are structured by using a cognitive map to determine the relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 36 publications
(21 reference statements)
1
26
0
1
Order By: Relevance
“…MAVT is a well-researched and well-founded methodology, and a relatively simple MCDA method. Indeed, research in Multi Attribute Decision Making has suggested the use of simple, understandable and usable approaches for solving decision-making problems (Ulengin et al, 2010). Other reasons for choosing MAVT to complete the present methodological framework are as follows: (i) since it is founded on fundamental axioms of rational choice (e.g.…”
Section: Multi Attribute Value Theorymentioning
confidence: 99%
“…MAVT is a well-researched and well-founded methodology, and a relatively simple MCDA method. Indeed, research in Multi Attribute Decision Making has suggested the use of simple, understandable and usable approaches for solving decision-making problems (Ulengin et al, 2010). Other reasons for choosing MAVT to complete the present methodological framework are as follows: (i) since it is founded on fundamental axioms of rational choice (e.g.…”
Section: Multi Attribute Value Theorymentioning
confidence: 99%
“…For the evaluation of sustainable transportation policy, an important research priority is the development of modeling and decision-making approaches from the system perspective (Ülengin, Kabak, Önsel, Ülengin & Aktaş, 2010;Fiksel, 2006), which focuses on interrelationships among components of the transportation system and treats the system's evolution as the result of interactions and feedbacks among those components. System Dynamics (SD), which was initially developed by Forrester from MIT in the 1950-1960s, is an -1712-Journal of Industrial Engineering and Management -http://dx.doi.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, sustainable transport system plays a great role (Ülengin et al [2], Hensher [3]). An environmentally sustainable transport system can be defined as "one where transportation does not endanger public health or ecosystems and meets needs for access consistent with use of renewable resources below their rates of regeneration and use of non-renewable resources below the rates of development of renewable substitutes (Browne et al [4]).…”
Section: Introductionmentioning
confidence: 99%